SISTEM PENJADWALAN RAPAT PIMPINAN UNIVERSITAS DENGAN METODE MATRIKS - Bambang Nurdewanto (Universitas Merdeka Malang, 2016)
Leadership Meeting is one of the regular activities carried out at a university. The participants of this meeting in addition to serving leader as well as a lecturer who daily burdened by student teaching activities . Often these participants complain because scheduled board meeting in conjunction with the teaching schedule in jurusan. Than it needs to be a method that is reliable and quick to perform effective scheduling by performing matrix method assisted by using the software. If using a calculation matrix operations manually adding any change or update data, requiring the repetition of a recount needs to be done carefully . But by using this software, the end result can be seen immediately, immediately formed matrix accumulation. Leaders who will be meeting participants can be chosen flexibly. Matrix data will be automatically updated after the meeting participants selected, so that the determination of the leadership meeting schedule will be more flexible and accurate. DOI: https://doi.org/10.26905/jtmi.v2i1.614